(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
This analysis delves into the evolving historical narratives and academic freedom in Ukraine and Russia during the Russo-Ukrainian conflict. Before 2014, Russia underwent a shift from post-Soviet intellectual freedom to increased control under Putin. Subsequent years witnessed political persecution, censorship, and a scholar exodus. The conflict intensified academic suppression in Russia from 2014 to 2023, targeting dissenters. Meanwhile, Ukraine experienced notable education changes, emphasizing national identity. This study reveals the intricate interplay between geopolitics and academic autonomy, showcasing the contrasting educational trajectories in both nations amidst the complex dynamics of the ongoing conflict.